Konstruksi Makna Identitas Mena Muria pada Kaus Oblong Kutikata - Soukotta, Ferdy Karel (Retorik: Jurnal Ilmu Humaniora, 2024)
This study aims to determine how the construction of the meaning of mena murias identity in the Kutikata catalog T-shirts managed by Revelino Barry. This brand offers Maluku identity and literacy information issues, one of which is mena muria. The focus of this research is to find out mena muria as a cultural identity whose meaning of identity does not change in meaning as an identity owned by RMS (Republic of South Maluku), and to find out Kutikatas role in constructing mena muris identity on the medium of T-shirts and social media. This research was conducted using a qualitative descriptive method with the analysis of Manuel Castells model of identity formation, namely resistance identity. This identity model is used by the researcher to reveal social actors, collective resistance and the formation of the Kutikata community. The data collection technique in this study used observation and in-depth interviews with five sources and then processed by researchers to obtain appropriate and accurate data. The results in this study indicate that the social actor who plays an important role in the construction of mena murias identity is Revelino Barry, with Kutikata as an identity-based movement and collective resistance carried out by actors in forming a collective communication network while sharing knowledge about identity, in this case regarding mena muria. The formation of a community then is seen from the dissemination of information online in the Kutikata catalog and offline discussions conducted by actors.